Answers

2014-10-19T00:42:06+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(1+tan 20)(1+tan 25)-2
=1 + tan 25 + tan 20 + tan20 
× tan25 - 2
=tan 20 + tan 25 + tan20 × tan 25 -1

using tan(A+B)=(tan A + tan B)/(1-tan A
×tan B)
⇒tan(A+B)×(1-tan A×tan B)=tan A+ tan B

take A=20, B=25
⇒tan(20+25)×(1-tan 20×tan 25)=tan 20 + tan 25
⇒tan(45)×(1-tan 20×tan 25)=tan 20 + tan 25
⇒1×(1-tan 20×tan 25)=tan 20 + tan 25
⇒1 - tan 20×tan 25=tan 20 + tan 25
⇒tan 20 + tan 25 + tan 20 × tan 25 - 1 = 0

So the required answer is 0.



3 5 3
explain the second step
just expand.(a+b)(c+d)=ac+ad+bc+bd
SIR IT IS 1- tan A
(1-tanA+tanB)
see the formula in your book...